How to Read and Interpret UV-VIS Spectrophotometric Results in Determining the Structure of Chemical Compounds - Restiani Alia Pratiwi; Asep Bayu Dani Nandiyanto (Indonesian Journal of Educational Research and Technology, 2022)
UV-VIS spectrophotometry is one of the methods used toperform qualitative and quantitative analysis of organic andinorganic compounds. However, until now there has been nofurther research that studies and describes the detailedanalysis of UV-VIS spectral data in terms of determining thestructure of chemical compounds. Therefore, this papercontains guidelines that are used as information on how toread and interpret data from the UV-VIS spectrum in termsof determining the structure of chemical compounds. Stepson how to analyze the UV-VIS spectrum are presented. Thispaper is expected to provide useful information forresearchers and novice students who are studying UV-VISspectrophotometry.